2022
DOI: 10.12688/f1000research.76191.2
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiredoxin-1 blood mRNA expression levels negatively correlate with hippocampal atrophy and cognitive decline

Abstract: Introduction: Cognitive decline, correlating with hippocampal atrophy, characterizes several neurodegenerative disorders having a background of low-level chronic inflammation and oxidative stress. Methods: In this cross-sectional study, we examined how cognitive decline and hippocampal subfields volume are associated with the expression of redox and inflammatory genes in peripheral blood. We analyzed 34 individuals with different cognitive scores according to Mini-Mental State Examination, corrected by age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Studies have also reported that CHRFAM7A [58], ACHE (acetylcholinesterase (Cartwright blood group) [305], HP (haptoglobin) [306], SELENBP1 [63], BASP1 [72], CHRNA1 [307], RPTN (repetin) [76], IL33 [308], TACR1[309], SHANK3 [310], ALOX12B [311], HPN (hepsin) [312], GFAP (glial fibrillary acidic protein) [84], CACNB2 [313], MYT1 [314], NOTCH3 [315], TERT (telomerase reverse transcriptase) [316], GNB3 [317], EGR3 [318], BSN (bassoon presynaptic cytomatrix protein) [319], CUX2 [320], GDF15 [321], CXCL8 [322], MAGI1 [95] and PAH (phenylalanine hydroxylase) [323] are necessary for BD development. S100A12 [324], CDH1 [325], S100A9 [326], ANK1 [327], KCNH2 [328], HP (haptoglobin) [329], FRMD4A [330], SNCA (synuclein alpha) [331], FBXO7 [332], PINK1 [333], B2M [334], KCNH3 [335], CA2 [336], FUZ (fuzzy planar cell polarity protein) [337], UBB (ubiquitin B) [338], C5AR1 [339], CBS (cystathionine beta-synthase) [340], F12 [341], TSPAN5 [342], NQO2 [343], NDUFA1 [344], SRXN1 [345], BASP1 [346], GPX1 [347], OLIG2 [348], EFHC2 [349], FOXA1 [350], PAX4 [351], BGN (biglycan) [352], IL33 [353], LRIG3 [354], GJA1 [355], SHANK3 [356], ARC (activity regulated cytoskeleton associated protein) [357], GFAP (glial fibrillary acidic protein) [358], UNC13A [359], MSTN (myostatin) [360], HSPG2 [361], TERT (telomerase reverse transcriptase) [362], GNB3 [363], L1CAM [364], CALB1 [365], RYR2 [366], MYO15A [367], MYH11 [368], GDF15 […”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that CHRFAM7A [58], ACHE (acetylcholinesterase (Cartwright blood group) [305], HP (haptoglobin) [306], SELENBP1 [63], BASP1 [72], CHRNA1 [307], RPTN (repetin) [76], IL33 [308], TACR1[309], SHANK3 [310], ALOX12B [311], HPN (hepsin) [312], GFAP (glial fibrillary acidic protein) [84], CACNB2 [313], MYT1 [314], NOTCH3 [315], TERT (telomerase reverse transcriptase) [316], GNB3 [317], EGR3 [318], BSN (bassoon presynaptic cytomatrix protein) [319], CUX2 [320], GDF15 [321], CXCL8 [322], MAGI1 [95] and PAH (phenylalanine hydroxylase) [323] are necessary for BD development. S100A12 [324], CDH1 [325], S100A9 [326], ANK1 [327], KCNH2 [328], HP (haptoglobin) [329], FRMD4A [330], SNCA (synuclein alpha) [331], FBXO7 [332], PINK1 [333], B2M [334], KCNH3 [335], CA2 [336], FUZ (fuzzy planar cell polarity protein) [337], UBB (ubiquitin B) [338], C5AR1 [339], CBS (cystathionine beta-synthase) [340], F12 [341], TSPAN5 [342], NQO2 [343], NDUFA1 [344], SRXN1 [345], BASP1 [346], GPX1 [347], OLIG2 [348], EFHC2 [349], FOXA1 [350], PAX4 [351], BGN (biglycan) [352], IL33 [353], LRIG3 [354], GJA1 [355], SHANK3 [356], ARC (activity regulated cytoskeleton associated protein) [357], GFAP (glial fibrillary acidic protein) [358], UNC13A [359], MSTN (myostatin) [360], HSPG2 [361], TERT (telomerase reverse transcriptase) [362], GNB3 [363], L1CAM [364], CALB1 [365], RYR2 [366], MYO15A [367], MYH11 [368], GDF15 […”
Section: Discussionmentioning
confidence: 99%